RAMADAN: A MONTH TO QUIT TOBACCO - Khan, Javaid (Journal of Postgraduate Medical Institute, 2017)
The holy month of Ramadan offers tobacco users a great opportunity to quit this addiction as people refrain from food, drinks and tobacco use from dawn to dusk. "Quit Tobacco Day" is being held on the first of Ramadan throughout the Muslim world including Pakistan. Every year millions of muslims get rid to tobacco addiction during this most prestigious month of Islamic calendar.